International multicentre study to validate the Segmental Sedimentation and Counting Technique (SSCT) for the surveillance of Echinococcus multilocularis in red fox - Gérald Umhang; Fanny Bastien; Christophe Caillot; Gunita Deksne; Jacek Karamon; Rebecca Davidson; Maira Mateusa; Małgorzata Samorek-Pieróg; Azzurra Santoro; Federica Santolamazza; Relja Beck; James O’Shaughnessy; et al. (Veterinary Parasitology, 2026)

Trophic Interactions Are Key to Understanding the Effects of Global Change on the Distribution and Functional Role of the Brown Bear - Pablo M. Lucas; Wilfried Thuiller; Lauren Talluto; Ester Polaina; Jörg Albrecht; Nuria Selva; Marta De Barba; Vincenzo Penteriani; Maya Guéguen; Niko Balkenhol; Trishna Dutta; Ancuta Fedorca; et al. (Global Change Biology, 2025)
Biotic interactions are expected to influence species' responses to global changes, but they are rarely considered across broad spatial extents. Abiotic factors are thought to operate at larger spatial scales, while biotic factors, such as species interactions, are considered more important at local scales within communities, in part because of the knowledge gap on species interactions at large spatial scales (i.e., the Eltonian shortfall). We assessed, at a continental scale, (i) the importance of biotic interactions, through food webs, on species distributions, and (ii) how biotic interactions under scenarios of climate and land‐use change may affect the distribution of the brown bear ( Ursus arctos ). We built a highly detailed, spatially dynamic, and empirically sampled food web based on the energy contribution of 276 brown bear food species from different taxa (plants, vertebrates, and invertebrates) and their ensemble habitat models at high resolution across Europe. Then, combining energy contribution and predicted habitat of food species, we modelled energy contribution across space and included these layers within Bayesian‐based models of the brown bear distribution in Europe. The inclusion of biotic interactions considerably improved our understanding of brown bear distribution at large (continental) scales compared with Bayesian models including only abiotic factors (climate and land use). Predicted future range shifts, which included changes in the distribution of food species, varied greatly when considering various scenarios of change in biotic factors, providing a warning that future indirect climate and land‐use change are likely to have strong but highly uncertain impacts on species biogeography. Our study confirmed that advancing our understanding of ecological networks of species interactions will improve future projections of biodiversity change, especially for modelling species distributions and their functional role under climate and land‐use change scenarios, which is key for effective conservation of biodiversity and ecosystem services.

Detection of Echinococcus spp. and other taeniid species in lettuces and berries: Two international multicenter studies from the MEmE project - Gérald Umhang; Fanny Bastien; Alexandra Cartet; Haroon Ahmad; Kees van der Ark; Rebecca Berg; Piero Bonelli; Rebecca K. Davidson; Peter Deplazes; Gunita Deksne; Maria João Gargate; Joke Van der Giessen; et al. (International Journal of Food Microbiology, 2025)

Transboundary gene flow and notes on philopatry in lynx populations of Estonia and Latvia: implications for conservation - Egle Tammeleht; Marju Keis; Jaanus Remm; Dainis Rungis; Janis Ozolins; Urmas Saarma (Conservation Genetics, 2025)

Impact of global environmental changes on the range contraction of Eurasian moose since the Late Pleistocene - Magdalena Niedziałkowska; Marcin Górny; Joanna Gornia; Danijela Popović; Mateusz Baca; Urszula Ratajczak-Skrzatek; Oleksandr Kovalchuk; Maciej Sykut; Małgorzata Suska-Malawska; Paweł Mackiewicz; Emilia Hofman-Kamińska; Rafał Kowalczyk; et al. (Science of The Total Environment, 2024)

Winter temperature and forest cover have shaped red deer distribution in Europe and the Ural Mountains since the Late Pleistocene - Magdalena Niedziałkowska; Karolina Doan; Marcin Górny; Maciej Sykut; Krzysztof Stefaniak; Natalia Piotrowska; Bogumiła Jędrzejewska; Bogdan Ridush; Sławomira Pawełczyk; Paweł Mackiewicz; Ulrich Schmölcke; Pavel Kosintsev; et al. (Journal of Biogeography, 2021)
Aim The Expansion‐Contraction model has been used to explain the responses of species to climatic changes. During periods of unfavourable climatic conditions, species retreat to refugia from where they may later expand. This paper focuses on the palaeoecology of red deer over the past 54 ka across Europe and the Urals, to reveal patterns of change in their range and explore the role of environmental conditions in determining their distribution. Location Europe and western Asia to 63°E. Taxon Red deer ( Cervus elaphus ). Methods We collected 984 records of radiocarbon‐dated red deer subfossils from the Late Pleistocene and the Holocene, including 93 original dates. For each deer sample we compiled climatic and biome type data for the corresponding time intervals. Results During the last 54 ka changes in red deer range in Europe and the Urals were asynchronous and differed between western and eastern Europe and western Asia due to different environmental conditions in those regions. The range of suitable areas for deer during the Last Glacial Maximum (LGM) was larger than previously thought and covered vast regions not only in southern but also in western and eastern Europe. Throughout the period investigated the majority of specimens inhabited forests in the temperate climatic zone. The contribution of forests in deer localities significantly decreased during the last 4 ka, due to deforestation of Europe caused by humans. Mean January temperature was the main limiting factor for species distribution. Over 90% of the samples were found in areas where mean January temperature was above −10°C. Main conclusions Red deer response to climatic oscillations are in agreement with the Expansion‐Contraction model but in contradiction to the statement of only the southernmost LGM refugia of the species. During the last 54 ka red deer occurred mostly in forests of the temperate climatic zone.

Low genetic polymorphism in the re-introduced Eurasian beaver (Castor fiber) population in Finland: implications for conservation - Terhi Iso-Touru; Otso Huitu; Miika Tapio; Jūratė Kučinskienė; Alius Ulevičius; Egidijus Bukelskis; Konstantin Tirronen; Fyodor Fyodorov; Danila Panchenko; Urmas Saarma; Harri Valdmann; Kaarina Kauhala (Mammal Research, 2020)
Background Reduction of genetic diversity can lead to reduced fitness of species, such as the loss of adaptability to changing environments. The native Eurasian beaver ( Castor fiber ) was hunted to extinction from Finland and many other countries in Europe in the nineteenth century. In Finland, the species was re-introduced in the 1930s with only a few individuals from Norway. Re-introductions were performed also in other countries of northern Europe and as a result, Eurasian beaver populations have undergone population bottlenecks leading to low levels of genetic diversity. Materials and Methods Here, 200 Eurasian beaver samples from Finland, Estonia, Lithuania, and Russian Karelia were investigated using 12 microsatellite markers to examine the level of genetic diversity and relationship between the populations. Results While Russian and Estonian populations were genetically the closest, the Finnish population was clearly distinct from all others and had the lowest genetic variability among the study populations. This may be deleterious to the population especially in a changing environment. Conclusions Genetic rescue could be the best solution to increase the genetic diversity and improve the future prospects of the population, although more studies are required to resolve the optimal source population.

Ongoing recovery of a brown bear population from a century-old severe bottleneck: insights from population genetic and spatially explicit analyses - Peeter Anijalg; Jaanus Remm; Egle Tammeleht; Marju Keis; Harri Valdmann; Urmas Saarma (Conservation Genetics, 2020)

Assessing the roles of wolves and dogs in livestock predation with suggestions for mitigating human–wildlife conflict and conservation of wolves - Liivi Plumer; Tõnu Talvi; Peep Männil; Urmas Saarma (Conservation Genetics, 2018)

Increased nest predation near protected capercaillie leks: a caveat against small reserves - Ragne Oja; Eliisa Pass; Egle Soe; Karli Ligi; Peeter Anijalg; Leidi Laurimaa; Urmas Saarma; Asko Lõhmus; Harri Valdmann (European Journal of Wildlife Research, 2018)

Large‐scale migrations of brown bears in Eurasia and to North America during the Late Pleistocene - Peeter Anijalg; Simon Y. W. Ho; John Davison; Marju Keis; Egle Tammeleht; Katalina Bobowik; Igor L. Tumanov; Alexander P. Saveljev; Elena A. Lyapunova; Alexandr A. Vorobiev; Nikolai I. Markov; Alexey P. Kryukov; et al. (Journal of Biogeography, 2018)
Aim Climatic changes during the Late Pleistocene had major impacts on populations of plant and animal species. Brown bears and other large mammals are likely to have experienced analogous ecological pressures and phylogeographical processes. Here, we address several unresolved issues regarding the Late Pleistocene demography of brown bears: (1) the putative locations of refugia; (2) the direction of migrations across Eurasia and into North America; and (3) parallels with the demographic histories of other wild mammals and modern humans. Location Eurasia and North America. Methods We sequenced 110 complete mitochondrial genomes from Eurasian brown bears and combined these with published sequences from 138 brown bears and 33 polar bears. We used a Bayesian approach to obtain a joint estimate of the phylogeny and evolutionary divergence times. The inferred mutation rate was compared with estimates obtained using two additional methods. Results Bayesian phylogenetic analysis identified seven clades of brown bears, with most individuals belonging to a very large Holarctic clade. Bears from the widespread clade 3a1, which has a distribution from Europe across Asia to Alaska, shared a common ancestor about 45,000 years ago. Main conclusions We suggest that the Altai‐Sayan region and Beringia were important Late Pleistocene refuge areas for brown bears and propose large‐scale migration scenarios for bears in Eurasia and to North America. We also argue that brown bears and modern humans experienced a demographic standstill in Beringia before colonizing North America.

Complete mitochondrial genomes and a novel spatial genetic method reveal cryptic phylogeographical structure and migration patterns among brown bears in north‐western Eurasia - Marju Keis; Jaanus Remm; Simon Y. W. Ho; John Davison; Egle Tammeleht; Igor L. Tumanov; Alexander P. Saveljev; Peep Männil; Ilpo Kojola; Alexei V. Abramov; Tõnu Margus; Urmas Saarma (Journal of Biogeography, 2013)
Aim Using sequences of complete mitochondrial genomes, our aims were: (1) to investigate the matrilineal phylogeographical structure, migration patterns and lineage coalescence times in a large, continuous population of brown bears ( Ursus arctos ); and (2) to develop a novel spatial genetic method to identify migration corridors and barriers. Location North‐western Eurasia: from eastern European Russia to the Baltic Sea. Methods We sequenced the complete mitochondrial genomes of 95 brown bears. The phylogeographical resolution of complete genomes was compared to that derived from subsets of the genome, including the most commonly used shorter sequences. We conducted network and Bayesian phylogeographical analyses and developed a novel, spatially explicit, individual‐based approach (called DR esD) for identifying migration corridors and barriers. Results Analysis of mitogenome sequences revealed five haplogroups, specific to particular geographical areas, exhibiting far greater resolving power than shorter sequences. Estimated coalescence times for the haplogroups ranged from 7.7 to 15.2 ka, suggesting that their divergence took place after the last glaciation. We found several migration trends, including a large westward migration from eastern European Russia towards Finland. We also found evidence of a potential barrier and a migration corridor in the south‐west of the study area. Main conclusions The use of complete mitochondrial genomes from a brown bear population in north‐western Eurasia allowed us to identify phylogeographical structure, signatures of demographic history and spatial processes that had not previously been detected using shorter sequences. These findings have implications for studies on other species and populations, especially those exhibiting low mt DNA diversity. The relatively recent divergence estimates for haplogroups highlight the significance not only of the last glaciation but also of climatic fluctuations during the post‐glacial period for the divergence of mammal populations in Europe. Our spatial genetic method represents a new tool for the analysis of genetic data in a geographical context and is applicable to any data that yield genetic distance matrices, including microsatellites, amplified fragment length polymorphisms ( AFLP s) and single‐nucleotide polymorphisms ( SNP s).

Sudden expansion of a single brown bear maternal lineage across northern continental Eurasia after the last ice age: a general demographic model for mammals? - MARJU KORSTEN; SIMON Y. W. HO; JOHN DAVISON; BERIT PÄHN; EGLE VULLA; MARIS ROHT; IGOR L. TUMANOV; ILPO KOJOLA; ZANETE ANDERSONE‐LILLEY; JANIS OZOLINS; MALGORZATA PILOT; YORGOS MERTZANIS; et al. (Molecular Ecology, 2009)
The brown bear has proved a useful model for studying Late Quaternary mammalian phylogeography. However, information is lacking from northern continental Eurasia, which constitutes a large part of the species’ current distribution. We analysed mitochondrial DNA sequences (totalling 1943 bp) from 205 bears from northeast Europe and Russia in order to characterize the maternal phylogeography of bears in this region. We also estimated the formation times of the sampled brown bear lineages and those of its extinct relative, the cave bear. Four closely related haplogroups belonging to a single mitochondrial subclade were identified in northern continental Eurasia. Several haplotypes were found throughout the whole study area, while one haplogroup was restricted to Kamchatka. The haplotype network, estimated divergence times and various statistical tests indicated that bears in northern continental Eurasia recently underwent a sudden expansion, preceded by a severe bottleneck. This brown bear population was therefore most likely founded by a small number of bears that were restricted to a single refuge area during the last glacial maximum. This pattern has been described previously for other mammal species and as such may represent one general model for the phylogeography of Eurasian mammals. Bayesian divergence time estimates are presented for different brown and cave bear clades. Moreover, our results demonstrate the extent of substitution rate variation occurring throughout the phylogenetic tree, highlighting the need for appropriate calibration when estimating divergence times.

Systematic position of Lythriini revised: transferred from Larentiinae to Sterrhinae (Lepidoptera, Geometridae) - Erki ÕUnap; Jaan Viidalepp; Urmas Saarma (Zoologica Scripta, 2008)
The tribe Lythriini is a small group of diurnally active geometrid moths consisting of a single Palaearctic genus Lythria with five species. The systematic placement of Lythriini has remained controversial: though traditionally it has been placed into the subfamily Larentiinae, a number of morphological characters link this tribe with the subfamily Sterrhinae. A molecular phylogenetic study was conducted to verify the systematic position of Lythriini, using sequences of both mitochondrial and nuclear genes: elongation factor 1α ( EF‐1α ), wingless ( wgl ), 28S rRNA expansion segment D2 ( 28S D2 ), cytochrome oxidase subunit 1 ( COI ) and NADH dehydrogenase subunit 1 ( ND1 ) (a total of 3784 bp). Phylogenetic analysis reliably demonstrated that Lythriini belong to the subfamily Sterrhinae. Therefore, we propose to remove tribe Lythriini from Larentiinae and unite it with Sterrhinae. Moreover, our analysis supports the monophyly of both Sterrhinae and Larentiinae. However, although both morphological data and interspecific genetic distances insinuated that Lythria cruentaria and L. sanguinaria are sister species, the latter formed a clade of sister taxa together with L. purpuraria .

Mitogenetic structure of brown bears ( Ursus arctos L.) in northeastern Europe and a new time frame for the formation of European brown bear lineages - URMAS SAARMA; SIMON Y. W. HO; OLIVER G. PYBUS; MARJU KALJUSTE; IGOR L. TUMANOV; ILPO. KOJOLA; ALEX A. VOROBIEV; NIKOLAI I. MARKOV; ALEXANDER P. SAVELJEV; HARRI VALDMANN; ELENA A. LYAPUNOVA; ALEXEI V. ABRAMOV; et al. (Molecular Ecology, 2007)
We estimated the phylogenetic relationships of brown bear maternal haplotypes from countries of northeastern Europe (Estonia, Finland and European Russia), using sequences of mitochondrial DNA (mtDNA) control region of 231 bears. Twenty‐five mtDNA haplotypes were identified. The brown bear population in northeastern Europe can be divided into three haplogroups: one with bears from all three countries, one with bears from Finland and Russia, and the third composed almost exclusively of bears from European Russia. Four haplotypes from Finland and European Russia matched exactly with haplotypes from Slovakia, suggesting the significance of the current territory of Slovakia in ancient demographic processes of brown bears. Based on the results of this study and those from the recent literature, we hypothesize that the West Carpathian Mountains have served either as one of the northernmost refuge areas or as an important movement corridor for brown bears of the Eastern lineage towards northern Europe during or after the last ice age. Bayesian analyses were performed to investigate the temporal framework of brown bear lineages in Europe. The molecular clock was calibrated using Beringian brown bear sequences derived from radiocarbon‐dated ancient samples, and the estimated mutation rate was 29.8% (13.3%−47.6%) per million years. The whole European population and Western and Eastern lineages formed about 175 000, 70 000 and 25 000 years before present, respectively. Our approach to estimating the time frame of brown bear evolution demonstrates the importance of using an appropriate mutation rate, and this has implications for other studies of Pleistocene populations.